PENGEMBANGAN BUKU CERITA ANAK BERMUATAN LITERASI EMOSI UNTUK PESERTA DIDIK SEKOLAH DASAR - Cyntia, - (2022)
This research is motivated by the results of a study of the importance of emotional literacy for students, but the limitations of literature in the form of children's story books containing emotional literature. The purpose of this study is to develop children's story books containing emotional literacy that can be used as literature on emotional literacy culture and can be used in learning at school, especially in learning literary appreciation in elementary schools. This study uses an Educational Design Research (EDR) research design with three research stages, namely (1) analysis and exploration stages; (2) design and construction stage; and (3) evaluation and reflection stage. The data collection techniques used were observation, interviews, documentation studies, three expert validation, product trials, and product response tests. The results of this development indicate that (1) the results of the analysis and exploration show a need analysis for the product developed by taking into account the emotional literacy aspects of students and the availability and criteria of children's story books; (2) the results of the design and construction show that the results of the feasibility of children's storybook products containing emotional literacy by (a) linguists on language and story structure are declared "appropriate", (b) pedagogical experts on curriculum aspects are declared "very feasible", and ( c) the illustration expert on the illustration aspect is declared "appropriate"; (3) the use of children's story books containing emotional literacy for elementary school students is declared "effective" to improve the emotional literacy of elementary school students because there is a significant difference between the results of the pretest and posttest data. In addition, the product developed received a positive response from the teacher who stated that children's story books containing emotional literacy could be used as learning support and introducing emotional literacy to students, and positive responses from students. The implications of this research are (1) children's story books containing emotional literacy support the cultivation of emotional literacy; (2) this children's story book can be used as a support for learning, especially in learning appreciation of children's literature in elementary schools.